Covariates of Identified Stress and Depression among Seasonal Farmworkers - Chaney, Beth H. (Int J Environ Res Public Health, 2017)
Many noted difficulties of farmworker life result in increased risk for stress and depression. To date, limited research has focused primarily on seasonal farmworkers; much of the prior research examines migrant farmworkers or both groups collectively. This study aims to: (1) describe levels of stress and depression among a sample of seasonal farmworkers; and (2) identify if covariates (age, gender, marital status, education level, years of residency, problems obtaining healthcare due to documentation, language barriers, transportation, costs, medical insurance, and stress level) are significant predictors of depressive symptoms. Survey data were collected from 150 Latino seasonal farmworkers. A hierarchical binary logistic regression was conducted to identify significant covariates. The results indicated that the only statistically significant covariates were health insurance coverage (p = 0.025) and stress (p = 0.008). Those farmworkers without health insurance were 1.8 times more likely than those with health insurance to possess depressive symptoms, while those demonstrating higher stress levels were over 7 times more likely to demonstrate symptoms of depression. The implications of the results are discussed in the manuscript.